2023
DOI: 10.1111/aogs.14570
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ductus venosus Doppler and cerebroplacental ratio for the prediction of adverse perinatal outcome in high‐risk pregnancies before and after 34 weeks

Abstract: Introduction The objective of the study was to compare the accuracy of the ductus venosus pulsatility index (DV PI) with that of the cerebroplacental ratio (CPR) for the prediction of adverse perinatal outcome at two gestational ages: <34 and ≥34 weeks' gestation. Material and methods This was a retrospective study of 169 high‐risk pregnancies (72 < 34 and 97 ≥ 34 weeks) that underwent an ultrasound examination of CPR, DV Doppler and estimated fetal weight at 22–40 weeks. The CPR and DV PI were converted into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…We could not find any benefit of DV Doppler for APO prediction in our study just as we could not find any differences in DV-PI between GDM pregnancies with and without CAPO. This is in line with Morales-Roselló et al, who recently reported DV-PI as a poor predictor for APO > 34 weeks of gestation in a high-risk population [18]. However, in contrast to their study collective, which is made up of different constellations of suspected PD, isolated GDM is a population in which DV Doppler pathology would be expected independently of PD purely based on the hyperglycemia-related cardiac dysfunction and not primarily based on progressively worsening PD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We could not find any benefit of DV Doppler for APO prediction in our study just as we could not find any differences in DV-PI between GDM pregnancies with and without CAPO. This is in line with Morales-Roselló et al, who recently reported DV-PI as a poor predictor for APO > 34 weeks of gestation in a high-risk population [18]. However, in contrast to their study collective, which is made up of different constellations of suspected PD, isolated GDM is a population in which DV Doppler pathology would be expected independently of PD purely based on the hyperglycemia-related cardiac dysfunction and not primarily based on progressively worsening PD.…”
Section: Discussionsupporting
confidence: 91%
“…Predictive performance of DV-PI (blue line) for the occurrence of CAPO. and deterioration of cardiac function can lead to raised atrial pressure and therefore abnormal flow in DV Doppler [17,18]. GDM-induced hyperglycemia leads to altered metabolism and fetal oxygen consumption, causing chronic fetal hypoxemia even in well glycemic-controlled GDM mothers [19].…”
Section: Discussionmentioning
confidence: 99%